Soil organic carbon and hydraulic properties in response to poultry manure and inorganic fertilizers in two tropical agro-ecologies - Uju Chinwe Osakwe; Sunday Ewele Obalum; Mohammed Moro Buri; Temitope Seun Babalola; Charles Arizechukwu Igwe; Jose Miguel Reichert (Universitas Sebelas Maret, 2025)
The response of soil structure to nutrient management may vary across environments. Poultry manure (PM) and/or inorganic fertilizers (IF) effects on soil pH, organic carbon (SOC), and hydraulic properties were assessed in derived savannah sandy-clay-loam Ultisols and rainforest sandy-loam Alfisols of Nigeria during 2013-2015. The Ultisols were inherently lower in soil pH and SOC than the Alfisols. Three PM rates (0, 5, and 10 t ha–1), each with four NPK/Urea-based IF levels (0, 50, 100, and 150%), were applied in 2013 and 2014 but not in 2015. At crop (maize) maturity, treatment affected the Ultisols more distinctly than the Alfisols. Regardless of IF level, PM10 and PM5 resulted in optimal soil pH (Ultisols) and hydraulic properties (Alfisols), respectively. Treatment PM10+IF50 produced overall optimal effects in 2014 and 2015, being among the highest for SOC in the Ultisols (13.30 and 10.23 g kg–1, respectively) and Alfisols (16.10 and 11.60 g kg–1, respectively). Its substitutes for soil pH and hydraulic properties were PM10+IF0 (Ultisols) and PM5+IF0 (Alfisols). Unlike most PM-based treatments, sole IFs, especially PM0+IF150, had pronounced soil-acidifying effects in the Ultisols. The SOC and permeability depended almost entirely on PM across IF levels. Soil pH and SOC were positively correlated with total porosity (Ultisols) and permeability (both soils), with r = 0.60-0.93 (Ultisols) and 0.42-0.66 (Alfisols). Effective PM+IF may not always outperform PM regarding soil pH/SOC, whose influence on soil hydraulic properties can be location-specific. This calls for pre-adoption validation of promising PM+IF options in new tropical agro-environments.